2012
DOI: 10.1681/asn.2011070738
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Identifies Vasopressin-Responsive Nuclear Proteins in Collecting Duct Cells

Abstract: Vasopressin controls transport in the renal collecting duct, in part, by regulating transcription. This complex process, which can involve translocation and/or modification of transcriptional regulators, is not completely understood. Here, we applied a method for large-scale profiling of nuclear proteins to quantify vasopressin-induced changes in the nuclear proteome of cortical collecting duct (mpkCCD) cells. Using stable isotope labeling and tandem mass spectrometry, we quantified 3987 nuclear proteins and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
81
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 43 publications
3
81
1
Order By: Relevance
“…Previous proteomic studies on vasopressin signaling in kidney collecting duct cells have suggested that the Wnt signaling pathway could also be involved in vasopressin-mediated AQP2 regulation (4,33,34). Recently, Schenk et al (34) demonstrated that vasopressin induced a change in the abundance of the transcriptional regulator ␤-catenin in the nuclear proteome of cortical collecting duct mpkCCD (clone 11) cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous proteomic studies on vasopressin signaling in kidney collecting duct cells have suggested that the Wnt signaling pathway could also be involved in vasopressin-mediated AQP2 regulation (4,33,34). Recently, Schenk et al (34) demonstrated that vasopressin induced a change in the abundance of the transcriptional regulator ␤-catenin in the nuclear proteome of cortical collecting duct mpkCCD (clone 11) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schenk et al (34) demonstrated that vasopressin induced a change in the abundance of the transcriptional regulator ␤-catenin in the nuclear proteome of cortical collecting duct mpkCCD (clone 11) cells. This finding potentially suggested that transcriptional regulator ␤-catenin could be involved in the transcriptional regulation in response to vasopressin stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteomic and transcriptomic data have been made publicly available in databases (3). Many of these studies have focused on whole cells (4-6), whereas several analyzed subcellular fractions (7)(8)(9)(10)(11)(12). Analysis of subcellular fractions is technically demanding, but it has the benefit of identifying low abundance proteins with important functions.…”
mentioning
confidence: 99%